(3EOGQI GdeMGaX GdGSJKeGQjI (B/s - (3NQjhT, MSfj Ydjs; (3GQTjO, YHO GdeYWj QVG s ((3YeGf(B: s (3OGQ RgQGf(B, s, 2012)
(3GdeaGgje GdYGeI ddeMaXI GdGSJKeGQjI , GdGhQGb GdeGdjI GdeJOGhdI aj CShGb GdfbO h GdeJOGhdI aj CShGb QCS GdeGd GdahQjI , eaghe GdYhGFO h GdeNGWQ h CfhGYgG , GOGQI GdeMGaX GdGSJKeGQjI , HhQUGJ GdChQGb GdeGdjI h HYV CReGJ GdeGdjI GdOhdjI (B: (3cjhe GdGKfjf GdCShO h CReI Shb GdefGN GdchjJj(B.s
Keywords: (3GdGOGQIs; (3GdESJKeGQs; (3GdGhQGb GdfbOjIs